Understanding the Construction of the Teaching Discourse in an On-Line Environment - Silva-Quiroz, J (2013)
The study of interactions regarding on-line environments for education is an area of research that has being developing during the last years in order to know the type of interactions that take place in discussion forums. Interactions analysis is important in order to know and to understand knowledge construction process in a virtual space. Qualitative and quantitative methodologies are used for the analysis of these interactions. This article presents the study of the interactions in a virtual learning environment for pedagogical training. The analysis of the interactions within a discussion forum is described from the interventions of the tutor and the participating teachers; messages and unit topics are used as analysis units and, in order to gain reliability, percentages are established with experts.
Keywords: Analysis of interactions; E-learning; Teacher training; Virtual learning environment